Glycolthermal synthesis of Bi2MoO6 nanoplates and their photocatalytic performance - Phattranit Dumrongrojthanath (2018)
© 2015 Elsevier B.V. Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanoplates were successfully synthesized by a glycolthermal method at 160 °C for 12 h. Pure orthorhombic Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanoplates were characterized by X-ray diffraction, scanning electron microscopy and UV-visible absorption spectroscopy. The effect of reaction temperature and length of reaction time on phase and morphology of the as-synthesized products was investigated. The 2.75 eV energy gap was investigated by UV-visible spectroscopy and was responsible for the photocatalysis. Photocatalytic performance of the Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanoplates evaluated through the degradation of rhodamine B under Xe light irradiation was 98.20% within 120 min.